The Impact of Fabric Types on The Size M Lantern Sleeves Test Result - Berlianda, Sarah; Ernawati, Ernawati (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The lantern sleeve is a variation of sleeve design characterized by its puffed appearance, similar to puff sleeves. The main difference lies in the construction; while puff sleeves are gathered, lantern sleeves are not. Lantern sleeves are composed of two separate pattern pieces upper and lower parts—that together create a distinctive volume. This study aims to analyze the effect of different fabric types on the outcome of lantern sleeves on a size M dummy. The fabrics used in this study include mikado, victori, and toyobo. A quantitative method was employed using a Likert scale questionnaire (1–4). Respondents consisted of two expert panelists and 15 trained panelists. The evaluation focused on three visual aspects: smoothness, shape stability, and volume of the sleeve. Data were analyzed descriptively and through the Friedman K-related samples test. The results showed that mikado fabric produced the best outcomes in all aspects: highly smooth (89.22%), highly stable (92.16%), and highly voluminous (95.59%). Statistical tests indicated a significant difference among fabric types (p < 0.05). Therefore, fabric selection significantly influences the final result of the lantern sleeve. Mikado fabric is recommended for optimal sleeve outcomes.